Rancang Bangun Software Aplikasi PCI (Pavement Condition Index) Untuk Evaluasi Kondisi Jalan - Setiawan, Arif; , Sri Sunarjono, MT, Ph.D; , Ir. Agus Riyanto, MT (2016)
PCI Method (Pavement Condition Index) used to approach the assessment of road conditions. The process of calculating the necessary PCI reading charts and tables reference to the large number which, if done manually tends to be inefficient / long, therefore we need a mechanism to calculate process automation for faster PCI. Therefore we need a mechanism to automate the process of counting, which is making a computer program to weave steps counting process PCI with Borland Delphi. In general, a visual language program has three main parts, namely data input, process, and outpu. The data used are secondary data from Sutanto (2010) were used as input data. Flow stages in the process of calculation by taking into account the elements - elements associated. , The results of the design / design Borland Delphi uses several components and variables - variables generates interface / display in the form of dialog boxes and buttons - buttons to input the data and include multiple notifications / notifications, so that a warning will appear if an error occurs during the data input process. Analysis and validation test Borland Delphi to manually process the PCI calculation produces no deviation.